LEARNING MANAGEMENT ISLAMIC EDUCATION - Fitriana, S.Pd.I (Journal of Educational Science Learning and Research, 2024)
The purpose of this study was to describe the management of Islamic Religious Education learning at SD Negeri 3 Sampoiniet. This research method uses a qualitative descriptive method. Data were collected by interview, observation, and documentation. Subjects of the study: principal, curriculum representative, Islamic Religious Education teacher and students. The results of this study are that Islamic Religious Education teachers at the beginning of the school year have prepared learning tools, implementation of Islamic Religious Education teacher learning using various methods and classroom management, learning evaluation, including cognitive, affective, and psychomotor, problems and solutions, Islamic Religious Education teachers held Islamic Religious Education KKG